Periodontitis and self‐reported halitosis among young adults from the 1982 Pelotas Birth Cohort. (14th February 2020) - Silva, Manuela F.; Nascimento, Gustavo G.; Leite, Fábio R.M.; Horta, Bernardo L.; Demarco, Flávio F.
Abstract: Objective: To investigate the association between periodontitis and self‐reported halitosis among young adults, and whether there is an interaction between the effects of smoking and periodontitis on halitosis. Methods: Data from the 1982 Pelotas birth cohort, Brazil, were used. The controlled direct effect of periodontitis on self‐reported halitosis, not mediated by tongue coating, was estimated using marginal structural modeling. In addition, an interaction between the effects of smoking and periodontitis on halitosis was also tested. Confounders comprised sociodemographic information, obesity, diabetes, and oral hygiene habits. Results: The controlled direct effect of periodontitis on halitosis not mediated by tongue coating showed that individuals with periodontitis had 90% higher risk of self‐reporting halitosis (RR 1.90) compared to healthy individuals. Individuals with mild periodontitis had twice the risk of reporting halitosis than periodontally healthy individuals (RR 2.31). We also found an interaction between the effects of smoking and periodontitis on halitosis, as noted among smokers with mild (RR 2.91) and moderate‐to‐severe periodontitis (RR 5.84). Conclusion: There is a controlled direct effect of periodontitis on halitosis not mediated by tongue coating. Additionally, an interaction between the effects of smoking and periodontitis on halitosis was also detected.